Cost-effect and ethical reasoning in radionuclide therapy dosimetry under the new EU BSS. (September 2016) - Santos, J.A.M.
Abstract : Introduction: Radionuclide therapy (RT) dosimetry is wide-ranging, sometimes complex, and always needs resource allocation. From Iodine-131 (e.g. hyperthyroidism) to Lutetium-177 (e.g. neuroendocrine cancers) or Itrium-90 (e.g. radioembolization), there is a broad range of radionuclides and activities for therapeutic use. Since each patient is unique, a personalized dosimetry approach can therefore be recommended. Purpose: New developments in the field, and the new EU BSS Directive, are approaching dosimetry in RT to dosimetry in External Radiotherapy. However, there is a price to attain this goal and it needs to be justified. Materials and methods: Beauchamp and Childress beneficence principle is evoked to justify dosimetry in almost every patient subjected to RT, although the cost of such procedures can be onerous for the majority of the already overloaded health care systems. This fact, together with necessarily limited available funding, can conflict with the principle of justice, stated by these authors, when allocating resources, leading to the need of rationing and ethical reasoning. Results: Dosimetry implementation according to the EU BSS Directive must be carefully considered for each particular patient and pathology. The same Directive also strongly reinforces the medical physics expert (MPE) as part of the therapeutic team for RT. This implies that MPE are fundamental elements in the process of decision whether dosimetry should or not be performed in each particular circumstance. Conclusion: MPE should be aware of the vast range of ethical values and reasoning behind clinical decision making, and a formal education in Bioethics should be pursued by these professionals. Disclosure: The author has no relevant financial or nonfinancial relationships to disclose.